Impact of Nursing–Midwifery Communication and Handover Quality on Maternal Safety Outcomes in Maternity Units - Alfuhiqi, Shuruq Mohammed M; Wasife Mohammad Sayah Alhazmi; Sultanah Saqer Helal Alruwaili; Alruwaili, Maha Mulhi A; Hanan Sharid Othman Alrwoelly; Mona Ali G Al Mustaneer; Taghreed Saleh H Albalhareth; Sultanah Musafiq Galap Alruwaili; Hanadi Salem K Alfuhiqi; Khulud Olayan Thuwaini Alruwaili; Majedh Madsher Alanzy (International Journal of Computational and Experimental Science and Engineering, 2024)
The quality of communication and handover processes between nursing and midwifery staff is a fundamental determinant of maternal safety outcomes in maternity units. Effective, structured communication acts as a critical layer of defense within the healthcare system, preventing errors by ensuring accurate information transfer, shared situational awareness, and aligned care plans during the dynamic and high-risk perinatal period. Conversely, failures in this dialogue—such as incomplete handovers, ambiguous messaging, or a culture that stifes psychological safety—create direct pathways to adverse events, including delayed responses to hemorrhage, sepsis, and hypertensive crises. Optimizing this interaction through standardized tools like SBAR, interdisciplinary training, and fostering a culture of open communication is therefore not merely an administrative concern but a vital clinical intervention essential for reducing preventable maternal morbidity and mortality.